ANALISIS USABILITY WEBSITE PERGURUAN TINGGI KOTA JAMBI DENGAN METODE ENTROPI DAN TOPSIS - IBNU SANI WIJAYA (Jurnal Processor, 2018)
The increasing number of universities that rely on academic websites is triggering the growth of organizations that try to rank academic websites based on the standard assessment of the quality of an academic website. Until now, many organizations are issuing the value of academic website rankings based on the standards they have created. Based on Webometrics, Academic Ranking of World Universities (ARWU), and THES, for example, they have different standards for assigning grades and ratings from academic websites. Of the above three authors will use the ranking of Webometrics as a comparison. Webometrics has four assessment criteria that each of these criteria is given its own weight, the highest total score will rank first in the ranking they will release. The four criteria of Webometrics assessment used and its weight are: visibility (V) with a weight of 0.5; size (S) with weight 0.2; richfiles (R) with weights 0.15 and scholar (Sc) weighing 0.15. The object of this research is five college website in jambi city which has been chosen by writer. Data collection will be done with a period of 6 months, then the data in the average for further processed by the method of Entropy to obtain the weights used and Topsis method to determine the rank obtained. The ranking results with both methods were then compared with the October 2017 Webometrics release using the Spearman test as a hypothesis feasibility test